PERBANDINGAN KUALITAS INFORMASI CITRA MRI CERVICAL T2 TSE SAGITAL DENGAN CSPINE COIL DAN HEADNECK COIL PADA KASUS HERNIA NUCLEUS PULPOSUS (HNP) - Devi Oktavia (Health Care Media, 2023)
Radiofrequency (RF) coil is a tool for sending and receiving frequency waves during an MRI scanner and RF coils are one of the most important components in terms of image quality. At Bali Mandara Hospital there are two types of coils that can be used for Cervical MRI examination. The purpose of this research is quality of sagittal T2 FSE cervical MRI image information with cspine coil and headneck coil in cases of hernia nucleus pulposus (HNP) and which coil is more optimal in displaying the quality of mri image information cervical T2 TSE sagittal hernia nucleus pulposus (HNP) cases. This research is a quantitative research with an experimental approach. Samples of 5 patients using two types of coils, namely cspine coil and headneck coil. The research was conducted at the Radiology Installation of Bali Mandara Hospital using a 1.5 Tesla MRI. The result obtained from the calculation is that the average value of SNR using cspine coil is 229.92, while the average value of SNR using a headneck coil is 289.71. From the results of these calculations showed a difference in the average SNR value of 59.79, therefore, the headneck coil have higher SNR value compared to the cspine coil. The conclusion of this study is that on the MRI examination of cervical T2 TSE sagittal, there ia a significant difference in image quality in terms of SNR between the use of cspine coil and headneck coil, and the use of headneck coil can increase the SNR value